Formative Assessment for Promoting Intrinsic Motivation in an EAP Reading Comprehension Course - Escobar Leiva, Ana Laura (2018)
This study aims to determine the extent to which formative assessmentinfluences performance in summative assessment and student attitudestowards reading academic texts in English. In a sample of 9 psychology major students at a public university in San José, Costa Rica, the study gathered data pertaining to learner performance in both formative and summative assessment as well as self-reported attitudes and perceptions in questionnaires administered after assessment. The results have revealed that formative assessment has positively influenced student performance in summative assessment, and that in turn it has promoted a more enthusiastic attitude towards reading academic texts in English.